Power yoga for athletes more than 100 poses and flows to improve performance in any sport - Vigue, Sean (Beverly, MA Fair Winds Press, 2015)
"Hockey, football, baseball, golf, swimming, lacrosse - whatever your sport of choice, yoga will help you to improve focus, flexibility, and performance. Power Yoga for Athletes is perfect for those who want a total body and mind workout. Yoga is the ideal cross-training tool and a perfect stand-alone exercise, whether you're looking to improve balance, focus, control, breathing, posture, or flexibility; strengthen your back, joints, or core; or reduce or heal from injury.Yoga benefits athletes of all types, helping you to improve your athletic prowess and hone new strengths. You'll find many poses ideal for the sport of your choice including: Running Swimming Cycling Golfing Baseball Basketball SoccerFootball/rugby HockeyTennisFeaturing more than 100 yoga poses from instructor Sean Vigue, Power Yoga for Athletes incorporates more than just poses. It describes a whole-body program for cross-training and conditioning. Each yoga pose features step-by-step directions, instructional photography, muscles being worked, overall benefits, and the sports for which each pose is ideal. Get the balance, strength, and focus you need to perform at your best"--Provided by publisher.
Includes index.
Keywords: Astanga yoga; Athletes -- Trainig of